Nonalcoholic fatty pancreas disease and Nonalcoholic fatty liver disease: more than ectopic fat. (12th August 2015) - Della Corte, C.; Mosca, A.; Majo, F.; Lucidi, V.; Panera, N.; Giglioni, E.; Monti, L.; Stronati, L.; Alisi, A.; Nobili, V.
Summary Objective The aim of this study was to evaluate the metabolic effects of fatty pancreas (nonalcoholic fatty pancreas disease – NAFPD) in a group of obese paediatric patients with nonalcoholic fatty liver disease (NAFLD). Methods We included 121 consecutive children with echographic evidence of hepatic steatosis. All patients underwent to abdominal ultrasound to evaluate pancreatic echogenic pattern. We divided the patients into two groups on the basis of the presence of fatty pancreas. In all patients liver function tests, lipid and gluco‐insulinemic profile were evaluated. A selected subset of patients (67) underwent to liver biopsy. Results Of these 121 patients, 58 showed NAFPD and 63 patients exhibited a normal pancreatic echogenic pattern. No differences were found in age, transaminases serum levels, lipid profile and pancreatic enzymes between the two groups. The patients with NAFPD had a significantly higher z‐BMI, fasting insulin, insulin resistance (HOMA‐IR) and lower ISI respect to the group without fatty pancreas. The patients with fatty pancreas showed a more advanced form of liver disease, with higher values of fibrosis, ballooning and NAS score with respect to the group without NAFPD. Conclusions Our study demonstrated that NAFPD is a frequent condition in obese paediatric patients affected by NAFLD. Our data suggest that pancreatic fat should not be considered an inert accumulation of fat, but as an additional factor able to affect glucose metabolism and severity of liver disease, increasing the risk of develop metabolic syndrome.